Histological disorders of neurons of phylogenetically different parts of the cerebral cortex in partial, subtotal, stepwise subtotal, and total cerebral ischemia - Bon, Lizaveta I.; Maksimovich, Nataliya Y. (Journal of Medical Science, 2021)
Aim. Measure of the histological changes in neurons in the parietal cortex and hippocampus of rats with partial, subtotal, stepwise subtotal, and total cerebral ischemia.Material and Methods. Studies were performed on 84 rats. Partial cerebral ischemia was modelled by ligation of one common carotid artery. Subtotal cerebral ischemia was modelled by ligation of both common carotid arteries. Stepwise subtotal cerebral ischemia was performed by sequential ligation of both common carotid artery with 7-day, 3-day or 1-day intervals. Total cerebral ischemia (CI) was modelled by decapitation.Results. When comparing the morphological changes of neurons in the parietal cortex and hippocampus, we observed that, with the aggravation of the severity of cerebral ischemia, there was a progressive increase in the number of hyperchromic shrivelled neurons and neurons with pericellular oedema. Modelling of more severe types of ischemic damage lead to pronounced morphological changes in neurons – a decrease in size, deformation of the perikaryon, and increase in the degree of neuronal chromatophilia with their wrinkling.Conclusions. The smallest morphological changes in neurons were noted in the partial cerebral ischemia groups and subgroup 1 of stepwise subtotal cerebral ischemia, with an interval between common carotid artery dressings of 7 days. The most obvious morphological changes were observed in the conditions of total cerebral ischemia after 1 day. Changes in the parietal cortex and hippocampus were unidirectional, but in the parietal cortex, which is most sensitive to oxygen deficiency, they were more pronounced.
Keywords: cerebral ischemia; parietal cortex; neurons; rats; hippocampus